CLINICAL AND DEMOGRAPHIC CHARACTERISTICS OF PATIENTS WITH UNCOMPLICATED LIVER ECHINOCOCCOSIS - M.K. GULOV; A.I. DZHABOROV; J.S. DODKHOEV; D.K. MUKHABBATOV; E.L. KALMYKOV (Avicenna Tajik State Medical University, 2021)
Objective: Analysis of clinical and demographic parameters of patients with uncomplicated liver echinococcosis (LE). Methods: The study included 182 patients who underwent only open surgery for LE. Primary LE was detected in 39.6% of patients, recurrence of the disease - in 40.1%, combined echinococcosis (CE) - in 20.3%. Clinical and demographic parameters such as gender, age, incidence of comorbidities, location of residence, and cyst size were considered. Results: Among the patients enrolled in the study 44.5% were males and 55.5% were females. The average age was 36.0±1.2 years. The average duration of the disease among male and female patients was 5.5±0.7 and 4.9±0.5 years, respectively (p>0.05). The width of the cysts was significantly larger in female patients compared to the male ones (p<0.05; Z=2.04). There were significantly more comorbidities in the female than in the male patients (p<0.05), however, there were no significant difference in the incidence of any concomitant disease. In the majority of patients (47.2%) cysts were <9 cm in size; followed by the cysts 9-15 cm wide (39%), and exceeding 15 cm (13.9%). In female patients' cysts <9 cm were found significantly more often than of any other size (p<0.001). Cysts <9 cm prevailed in residents of urban areas (p<0.01), while in rural areas predominance of cysts ≥9 cm was observed (p<0.01). CE was diagnosed in 70% of female patients, allowing us to consider female gender as a risk factor for the development of this form of the disease. In male patients with combined cysts their diameter in the liver <9 cm was found significantly more often (p<0.05) than cysts of larger size; while the incidence of the cysts <9 cm and ≥9 cm in diameter did not differ in male and female patients. Patients with recurrent form of LE in 50% of cases applied for surgical treatment of cysts ≥9 cm. In rural areas, the number of patients with recurrent cysts <9 cm prevailed over cysts of ≥9 (p<0.001), while in city dwellers recurrent cysts ≥9 tended to predominate.Conclusion: The study demonstrated that young age is predominantly affected by LE. Frequency of surgical visits of patients with large and giant cysts is high. The female gender may be considered to be a risk factor for CE. Conclusion: The study demonstrated that young age is predominantly affected by LE. Frequency of surgical visits of patients with large and giant cysts is high. The female gender may be considered to be a risk factor for CE.